Intrauterine Perfusion of Autologous Platelet-Rich Plasma Before Frozen-Thawed Embryo Transfer Improves the Clinical Pregnancy Rate of Women With Recurrent Implantation Failure - Xu, Yangying; Hao, Cuifang; Fang, Jianye; Liu, Xiaoqiang; Xue, Pingping; Miao, Ruichao (Frontiers in Medicine, 2022)
Objective: To evaluate whether the intrauterine perfusion of platelet-rich plasma (PRP) before frozen-thawed embryo transfer (FET) improves the pregnancy outcomes of patients with repeated implantation failure (RIF). Methods: This retrospective study included 288 infertile women with RIF history after undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment from October 1, 2019 to January 1, 2021 at Qingdao Women and Children’s Hospital. Patients were divided into two groups according to whether they had received PRP intrauterine perfusion before embryo transfer in FET cycles. 138 patients were in the treatment (PRP) group and 150 patients were in the control group. The primary outcome measure was the live birth rates and the secondary outcome measures were clinical pregnancy rates, positive β hCG rates, miscarriage and implantation rates. Results: No significant differences in baseline demographic and clinical characteristics were observed between the two groups. Overall, patients in the PRP group achieved a significantly higher live birth rate (41 women; 29.71% vs 27 women; 18%) and clinical pregnancy rate (50 women; 36.23% vs 37 women; 24.67%) than patients in the control group. The positive β hCG of the PRP group is also significantly higher than that of the control group. In addition, compared with the control group, the PRP group had a higher implantation rate and a lower spontaneous abortion rate, but these differences were not statistically significant.